Precise determination of dolomite content in marine sediments. (10th October 2022) - Wurgaft, Eyal; Wang, Zhaohui Aleck; Shalev, Netta; Morag, Navot; Golan, Rotem; Gavrieli, Ittai
Abstract: Dolomite (CaMg[CO3 ]2 ) is a common rock‐forming mineral. Nevertheless, its mechanisms of formation and the factors that cause dolomite concentration variations within the sedimentary records constitute long‐standing geochemical questions. In addition, the flux of Mg 2+ leaving the ocean by the formation of dolomite is a controversial question, with some studies arguing that dolomite formation is a negligible Mg 2+ sink in the modern ocean, while others show that it constitutes more than 50% of the total Mg 2+ removal rate. An important factor that impedes the resolution of the dolomite Mg 2+ flux is the lack of analytical methods with adequate precision and detection limit to directly measure minute quantities of authigenic dolomite in marine sediments. Here, we present a new analytical method for direct, precise measurement of dolomite content in marine sediments. The method is based on sequential leaching of carbonate minerals in acid and tracks the CO2 emitted by the dissolution. Based on the measurement of gravimetric standards of calcite and dolomite, the method's detection limit and precision were determined as better than 0.2 and ± 0.2 dry wt% of dolomite, respectively. The method out‐performed dolomite quantification made by x‐ray diffraction and by inductive coupled plasma mass‐spectrometry, which provided precision of ± 2 and ± 1 dry wt%, respectively. Measurements of the dolomite content in modern sediments from the seafloor below the oligotrophic Eastern Mediterranean and the eutrophic Mississippi plume, and in clayey‐silty alluvial soil from south‐eastern Israel, demonstrated that the aforementioned precisions are also valid for natural samples.